Predictors of academic progression and desire to continue education for undergraduate and graduate nursing students: Cross-sectional study and a nested follow-up study. (April 2022) - Bokan, Ivana; Buljan, Ivan; Marušić, Matko; Malički, Mario; Čivljak, Marta; Marušić, Ana
Abstract: Background: There is conflicting evidence on predictors of nursing degree completion. Identification of predictors of student desire to continue their education could be important in developing strategies for encouraging and supporting students to complete their university-level nursing education. Aim: To explore the factors associated with the enrollment in the first graduate year of nursing studies, progression from the first to the third year of university undergraduate nursing study, and the desire of third-year undergraduate students to continue nursing education at the graduate level. Participants and methods: A cross-sectional study involving 351 first- and third-year undergraduate and first-year graduate nursing students from three cohorts of the University of Split Department of Health Studies and one generation of first- and third-year undergraduate nursing students from the Catholic University of Croatia, Zagreb. We collected sociodemographic data on the participants, their opinions about their education, and scores on nine psychological questionnaires: performance self-efficacy, academic self-efficacy, perseverance, attitudes towards science, self-respect, motivation, dispositional hope, future time perspective, and perceived personal incompetence. Results: More than half of third-year undergraduate students wanted to continue their nursing studies at the graduate level, but they did not progress to the graduate degree studies immediately after finishing their undergraduate studies. None of the assessed characteristics predicted the desire of the final undergraduate year students to continue nursing education at the graduate level. In a nested follow-up study of a cohort of undergraduate students, we observed an increase in student attitudes towards science, extrinsic and intrinsic motivation, future orientation, and a decrease in perceived personal incompetence. Conclusion: Our results demonstrate that immediate progression to graduate level of nursing education, although perceived as desired, is not achieved by undergraduate nursing students. Interventions focusing on motivation, future orientation, and personal competence need to be explored as a way to promote academic progression in nursing.